Functional Balance and Motor Impairment Correlations with Gait Parameters during Timed Up and Go Test across Three Attentional Loading Conditions in Stroke Survivors - Haidzir Manaf; Maria Justine; Mazlifah Omar (Stroke Research and Treatment)
The aim of this study was to determine whether stroke survivor’s gait performance during dual-task Timed Up and Go (TUG) test is correlated with the level of functional balance and motor impairment. Thirty stroke survivors (22 men, 8 women) were recruited for this study. The level of functional balance (Berg Balance Scale) and motor impairment (Fugl-Meyer assessment lower extremity) were assessed prior to the TUG test. TUG test was conducted under three attentional loading conditions (single, dual motor, and dual-cognitive). The time and number of steps were used to quantify gait parameters. The Spearmen’s rank correlation coefficient was used to evaluate the relationship between these variables. There was moderate to strong negative correlation between functional balance and gait parameters (range −0.53 to −0.73, P<0.05). There was a weak negative correlation observed between the time taken to complete the single task and motor impairment (rs=-0.43; P=0.02) dual motor task and motor impairment (rs=-0.41; P=0.02). However, there were no significant correlations between lower limb motor impairment and the number of steps in all conditions. These findings suggest that functional balance may be an influential domain of successful dual-task TUG in stroke.